A Method of Reducing Motor Vibration: Natural Frequency, Damping Ratio, and Vibration Analysis of CFRP Motor Frame. (11th January 2020) - Zhang, Jinguang; Yang, Hairu; Li, Xiong; Ye, Wei
Abstract : The existing motor frame is made of metal materials. In this paper, a carbon fiber reinforced plastic (CFRP) motor frame, which uses material damping to reduce vibration amplitude, which is proposed to design and manufacture low-vibration motors. The damp ratio of the CFRP motor frame is calculated by the damp prediction model based on strain energy, which is verified by the combination of the finite element method and experiment. The vibration characteristics of the CFRP frame motor are studied experimentally and compared with that of the metal frame motor. The results show that the CFRP frame motor has good vibration reduction. The amplitude reduction is up to 5 times higher than that of the metal motor frame, which proves that the damping vibration reduction of the CFRP motor frame has a good application value.